PENGARUH PERCEIVE QUALITY, COUNTRY OF ORIGIN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MEBEL PADA CV. GADING MAKMUR DI JEPARA - Satriyo, Guntur Adi; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2016)
Along with the growth and development of the furniture business in Indonesia which has increased Â very Â rapidly. Â The Â number Â of company Â that Â offer Â furniture Â product Â are Â increasing. Particularly at â€œGading Makmurâ€ company that wood based processed wood products. Increasing competition Â between Â furniture Â company to Â sell Â their Â products Â , Â causingÂ  Gading Â Makmur Companyâ€™s sales decline. Gading Makmur should be able to use the best marketing strategies to stay afloat.This Â study Â uses Â five Â variables: Â perceive Â quality, Â country Â of Â origin, Â promotion, Â and purchasing decisions. This research hypothesis testing using the data of 34 respondents. The analysis technique used in this research is to use a software program Statistical Package for Social Science (SPSS) 23.The result of this study indicate that variable perceive quality, country of origin, and promotion are positively affect to purchase decision.